How the cognitive reserve interacts with β-amyloid deposition in mitigating FDG metabolism: An observational study. Issue 16 (April 2017) - Carapelle, Elena; Serra, Laura; Modoni, Sergio; Falcone, Michele; Caltagirone, Carlo; Bozzali, Marco; Specchio, Luigi Maria; Avolio, Carlo
Abstract : Abstract: This observational study had the aim to assess the interaction between cognitive reserve (CR) and cerebrospinal fluid β-amyloid1-42 (Aβ1-42 ) in modulating brain [18F]fluorodeoxyglucose positron emission tomography (FDG-PET) metabolism in patients with moderate Alzheimer disease (AD). Twenty-seven patients with probable AD and 25 neurological normal subjects (NNS) entered the study. All participants had an FDG-PET scan, and AD patients also received a lumbar puncture to measure Aβ1-42, 181p-tau, and Tau concentrations. Based on years of formal education, AD patients were classified as highly educated-AD (years of formal education >5) or less educated-AD (years of formal education <5). By using a voxel-wise approach, we first investigated differences in the cerebral glucose uptake between AD and NNS, then we assessed the interaction between level of education (a proxy of CR) and cerebrospinal fluid biomarkers on FDG-PET metabolism in the patient groups. Significantly lower glucose uptake was observed in the posterior cingulate gyrus, in the precuneus, in the inferior and medial temporal gyrus, and in the inferior parietal lobule of AD patients compared with NNS. A significant interaction was found between CR and Aβ1-42 values on brain metabolism in the inferior and medial temporal gyrus bilaterally. The AD patients with higher CR level and marked signs of neuropathology showed glucose hypometabolism in regions typically targeted by AD pathology. This finding supports the hypothesis that CR partially compensates for the effect of Aβ plaques on cognitive impairment, helps in patients' clinical staging, and opens new possibilities for the development of nonpharmacological interventions. Abstract : Supplemental Digital Content is available in the text